KEDUDUKAN KREDITOR SEPARATIS, PREFEREN, KONKUREN, PEMEGANG POLIS, DAN PESERTA DALAM PEMBAGIAN HARTA PAILIT PERUSAHAAN ASURANSI DI INDONESIA - Bhakti Setiawan, Iwan; Lumban Gaol, Selamat (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
The bankruptcy of insurance companies creates complex issues in the distribution of bankrupt assets, particularly regarding the position of various parties with claims on the company's assets. The Insurance Law grants priority to policyholders, yet there remains ambiguity concerning the status of secured creditors, preferred creditors, and concurrent creditors in the bankruptcy process. This study aims to analyze the regulation of insurance company bankruptcy under Indonesian bankruptcy law and examine the position of various creditors and participants in the distribution of bankrupt assets. This research employs a normative juridical method with a statutory approach and case studies on the bankruptcy of insurance companies in Indonesia. The findings indicate that overlapping regulations often lead to disputes over the order of payment priority, potentially hindering the fair resolution of bankruptcy cases. Therefore, regulatory harmonization is necessary to establish legal certainty and better protection for all stakeholders involved in the bankruptcy process of insurance companies.